Penyuluhan Literasi Digital Mengenai Risiko Pinjaman Online Ilegal dan Perjudian Online - Aris Sugiarto; Sriyatun Sriyatun; Niken Saptarini; Suparman Suparman; Sofyan Hariadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Illegal online loans (pinjol) and online gambling (judol) have become a destructive nationwide phenomenon that threatens the social and economic stability of society. This community service activity aims to increase literacy and awareness of the dangers of these two practices in Jorok Village, Sumbawa Regency, a community with a unique economic vulnerability profile due to its dependence on the agricultural sector and significant unemployment rates. The method used was participatory and interactive direct counseling, involving material presentation sessions, group discussions, and case study analysis with participants from the Karang Taruna youth organization and mothers who are members of the Family Welfare Empowerment (PKK) program. The results of the activity showed a substantial increase in participants' understanding of the characteristics of illegal online lending, its modus operandi, and the multidimensional impacts of gambling addiction. Participants became better able to identify risks and learn mitigation measures to protect themselves and their families. This increase in literacy is expected to become the foundation for building community resilience in the face of financial crime threats in the digital era.